HPB P38 Bile duct injuries during cholecystectomy – Experience of referrals to a tertiary centre over a 7 year period. (7th December 2022) - Thillai, Manoj; Reetoo, Salil; White, Molly; Nicoll, Kenneth; Thomasset, Sarah
Abstract: Background: Laparoscopic Cholecystectomy is a common procedure performed both in elective & emergency setting for gall stone disease. Current literature states that the incidence of bile duct injuries is between 0.5–1.5%. These are iatrogenic catastrophe associated with significant perioperative morbidity, mortality, reduced long-term survival and reduced quality of life. Early identification and referral is key in help managing these injuries. In delayed cases, the choice and timing of the appropriate reconstructive procedure have a critical role in long-term prognosis. Methods: A retrospective analysis of all patients referred to the Royal Infirmary of Edinburgh between 2014 and 2021 was undertaken. All patients referred with suspected bile duct injuries were included in the study. Strasberg – type A (cystic duct leak), bile leaks following subtotal cholecystectomy and trauma were excluded. All injuries were classified according to the Strasberg classification. Results: A total of 34 patients were identified during the study period. Five patients (15%) had previously had abdominal surgery. Six patients (18%) had CBD stones at the time of cholecystectomy. Twenty one patients (62%) who sustained a bile duct injury were undergoing elective surgery. Bile duct injury was identified intraoperatively in 21 (62%) of cases. Eighteen patients (52%) were referred immediately, within 24 hours of the injury. Eight patients were referred early (within 72 hours) and eight patients were referred late (>10 days since injury). An E2 injury was most commonly seen, with 11 patients having this type of injury, followed by an E1 injury which was seen in 7 patients. An arterial injury was seen in 4 patients. A hepaticojejunostomy was the most commonly performed surgical procedure (22 out of 27 patients treated surgically). Immediate repair (within 72hours) was performed in 18 patients and this group of patients had the shortest hospital stay (10 days) and lowest long-term complication rate (5%). Conclusions: The majority of bile duct injuries that were referred happened during elective cholecystectomies. Significant delays in the identification of bile duct injuries and referral to tertiary centres persist. These delays continue to have a significant impact on hospital stay and long-term complications rates.